Whispering neurons fuel cortical highways - Schinder, Alejandro Fabián (2018)
Synaptic communication accelerates neuronal migration in the developing brain. The mammalian neocortex is one of the most intricate entities found in nature, both in terms of structure and function. It is the brain region responsible for the execution of high-order functions, including sensory perception, motor control, cognition, and speech. Its development is equally complex because it requires that millions to billions (depending on the species) of neurons assemble in distinct layers and connect with exquisite precision to perform complicated information processing operations. During embryonic development, formation of the cerebral cortex involves the migration of excitatory neurons generated in the ventricular zone toward the cortical plate, where they establish their final position in six well-defined horizontal layers consisting of different types of neurons and architecture. Along this migratory phase, developing neurons undergo a morphological transition from multipolar shape to bipolar morphology. Bipolar neurons exhibit faster locomotion, quickly reaching their final destination. On page 313 of this issue, Ohtaka-Maruyama et al. (1) reveal that this important switch to bipolar neurons is influenced by glutamate release from neurons located at the subplate, just beneath the cortical plate. Subplate neurons trigger this transformation by making transient synaptic contacts with multipolar neurons in transit to the cortical laminae. Understanding this process is important because disruption of neocortical migration results in several human neuro-developmental diseases.